Characteristic of Chronic Kidney Disease (CKD) Patients Routinely Treated with Hemodialysis in dr Tjitrowardojo Local Hospital, Purworejo, Central Java, Indonesia - Wiwit Sugiarti; Sri Nabawiyati Nurul Makiyah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Chronic Kidney Disease (CKD) is the main cause of hemodialysis therapy. This research aims to study the characteristic of the Chronic Kidney Disease patients who routinely undergo hemodialysis (HD) therapy. Observational research with the cross-sectional design is conducted to the chronic kidney disease patients routinely treated with hemodialysis in the Dr Tjitrowardojo Hospital in Purworejo. The respondents’ characteristics include demography, vital sign, chronic kidney disease causes, lifestyle, pain, and insomnia. Product Moment Pearson correlation test is used to test the data. The research’s result shows that the majority of the respondents are men 22 people (61.1%), aged 40-55 years old 17 people (38,9%), High School graduate 18 people (50%), working 25 people (69,4%), and are married 34 people (88,9%). The majority of the respondents do not smoke 33 people (91,7%), do not drink coffee 25 people (69,4%), do not exercise 32 people (88,9%), and suffered CKD due to hypertension 25 people (69,4%). The majority of the respondents, 24 people, have undergone HD for 1-5 years and every HD treatment, the duration is 4,5 hours. They have low Hb level (< 12 gr/dl), normal albumin level (3,5 – 5,2 g/dl), suffered moderate pain and insomnia (28 people). Respondents’ characteristics correlated strongly are the habit of drinking medicine, pain and insomnia. The conclusion is a smoking habit, pain, and insomnia is the closest characteristics linked to chronic kidney disease patients who routinely undergo hemodialysis. Keywords: Characteristic, Chronic Kidney Disease, Hemodialysis, Pain, Insomnia